The Effect of the Combination of ABC Running Drill and Hexagon Drill Exercises on Increasing the Agility of Men’s Futsal Athletes - Mahendra Yanuarsyah; Dede Rohmat Nurjaya; Angga M Syahid (Universitas Negeri Semarang, 2025)
Agility is a very important physical component in futsal, where the ability to change direction quickly and accurately determines the performance of athletes on the field. This study aims to determine the effect of the combination of ABC Running Drill and Hexagon Drill exercises on increasing the agility of male futsal athletes. This study uses an experimental design with a pre-test and post-test approach. The study population was male futsal athletes from Al Azhar 5 Islamic High School Cirebon with a sample of 15 athletes. Agility was measured using the Agility T-Test before and after the intervention in the form of a combination of ABC Running Drill and Hexagon Drill exercises for six weeks with 2 meetings per week. The data were analyzed using the Shapiro-Wilk normality test. The results showed a significant increase in agility with a decrease in the average travel time from 13.48 seconds in the pretest to 10.90 seconds in the posttest (difference of 2.58 seconds). All study subjects who were initially in the “poor” category (>12.5 seconds) experienced an improvement in performance with a posttest time range between 9.61-11.84 seconds. The data had a normal distribution based on the Shapiro-Wilk test (p-value > 0.05) and showed a decrease in standard deviation from 5.62 to 3.59, indicating an improvement in performance consistency between athletes. The combination of ABC Running Drill and Hexagon Drill exercises has proven to be effective in significantly increasing the agility of male futsal athletes. This training method can be implemented as an effective training strategy to develop the agility skills of futsal athletes, especially for athletes with low initial agility performance.